ANALISIS EKONOMI MELALUI OPTIMALISASI BUM DESA MARO KARYA DESA MARAPOKOT KECAMATAN AESESA KABUPATEN NAGEKEO PROVINSI NUSA TENGGARA TIMUR - Tristi Sintawati; Rini Raharti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Maro Karya Village-Owned Enterprises was used as an example Village-Owned Enterprises by the Nagekeo Regency Village Community Empowerment Service because of its success in developing businesses in the agricultural production sector. This research aims to find out how to optimize the development strategy for Maro Karya Village-Owned Enterprises, Marapokot Village, Aesesa District, Nagekeo Regency, East Nusa Tenggara Province. This research uses qualitative descriptive methods and SWOT analysis. SWOT analysis is very helpful in analyzing research to determine the strategy carried out by Maro Karya Village-Owned Enterprises. This data research comes from observations, interviews, questionnaires and documentation. From the results of this research, it was found that the growth and development of the Village-Owned Enterprises in Maro Karya was going well because the strategy carried out was correct so that it could provide optimal results.